Effectiveness, Safety and Obedience of Dienogest and Leuprolide Acetate in Postlaparoscopic Endometriosis Patients: Efektivitas, Keamanan dan Kepatuhan terhadap Dienoges dan Leuprolide Asetat pada Pasien Endometriosis Pascalaparoskopi - Joko P. Purwanto; Yusuf Effendi; Heriyadi Manan; Theodorus (Indonesian Journal of Obstetrics and Gynecology, 2020)
Abstract Objective: Comparing therapeutic effectiveness, safety profile, and adherence between Dienogest and postoperative Leuprolide Acetate in women with endometriosis who underwent laparoscopy. Methods: This study was a randomized clinical trial comparing the open label study to compare the effectiveness of therapy, safety profile, and obedience between postoperative dienogest and leuprolide acetate in women with endometriosis who underwent laparoscopy. Result: From the statistical test it was found that there was effectiveness of dienogest after 4 weeks of therapy (p = 0.004), after 8 weeks of therapy (p = 0.004) and after 12 weeks of therapy (p = 0.004). In the leuprolide acetate group it was also found that there was effectiveness of administration after 4 weeks of therapy (p = 0.004), after 8 weeks of therapy (p = 0.004) and after 12 weeks of therapy (p = 0.003). There was no difference in systolic blood pressure (p = 0.481), diastolic blood pressure (p = 1,000) and pulse frequency (p = 0.125) breath frequency (p = 1,000) and temperature (p = 0.236) between patients who received dienogest and leuprolide acetate. From the statistical analysis it was found that there were no differences in side effects in patients who received dienogest and leuprolide acetate (p = 0.238). Conclusion: There was no difference in therapeutic effectiveness, and the safety profile assessed by side effects as well as obedience of postoperative Dienogest and Leuprolide Acetate in endometriosis women undergoing Laparoscopy because in both groups there was a decrease in VAS scores from week to week. Key Word: Dienogest, Leuprolide Acetate, Endometriosis, Post-Laparoscopy, Therapy Abstrak Tujuan: Membandingkan efektivitas terapi, profil keamanan, dan kepatuhan antara Dienogest dengan Leuprolid Asetat pascaoperatif pada wanita endometriosis yang menjalani Lapararoskopi. Metode: Penelitian ini merupakan uji klinik acak berpembanding dengan open label study untuk membandingkan efektivitas terapi, profil keamanan, dan kepatuhan antara dienogest dan leuprolid asetat pascaoperatif pada wanita endometriosis yang menjalani lapararoskopi. Hasil: Dari uji statistik didapatkan hasil terdapat efektivitas pemberian dienogest setelah 4 minggu terapi (p = 0,004), setelah 8 minggu terapi (p = 0,004) dan setelah 12 minggu terapi (p = 0,004). Pada kelompok leuprolid asetat juga didapatkan hasil terdapat efektivitas pemberian setelah 4 minggu terapi (p = 0,004), setelah 8 minggu terapi (p = 0,004) dan setelah 12 minggu terapi (p = 0,003). Tidak terdapat perbedaan tekanan darah sistolik (p = 0,481), tekanan darah diastolik (p = 1,000) dan frekuensi nadi (p = 0,125) frekuensi napas (p = 1,000) dan suhu (p = 0,236) antara pasien yang mendapatkan dienogest dan leuprolid asetat. Dari analisa statistik didapatkan hasil tidak terdapat perbedaan efek samping pada pasien yang mendapatkan dienogest dan leuprolid asetat (p = 0,238). Kesimpulan: Tidak terdapat perbedaan efektivitas terapi, dan profil keamanan yang dinilai dari efek samping serta kepatuhan Dienogest dan Leuprolid Asetat pascaoperatif pada wanita endometriosis yang menjalani Lapararoskopi karena pada kedua kelompok terdapat penurunan VAS skor dari minggu ke minggu.